Improving the adsorption capacity and solid structure of natural volcanic soil using a foaming-sintering process based on recycled polyethylene terephthalate (PET) - Navia, Rodrigo (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2007)
The volcanic soils of southern Chile have demonstrated a high capacity to adsorb environmental pollutants, but for an industrial application, a stable solid material is necessary. The objective of this work was to produce a stable ceramic material through a process involving volcanic soil-polyurethane foam produced with recycled polyethylene terephthalate (PET)-polyols, and further thermal treatment. The selected foam formulation with 35.4% volcanic soil (< 63 microm) seems to be the most suitable for thermal treatment, with temperature steps at 700, 850, 1000 and 1200 degrees C. The porous ceramic material obtained has a stable solid form and an improved chlorophenols adsorption capacity (comparable to natural zeolites) that makes it suitable for advanced wastewater treatment and landfill leachate depuration